Improved Survival of Elderly-fit Patients With Acute Myeloid Leukemia Requiring Intensive Therapy: 3-Year Multicenter Analysis From TALWG - Weerapat Owattanapanich (2018)
© 2018 Elsevier Inc. Elderly patients with acute myeloid leukemia (AML) have a poorer prognosis than younger patients from previous studies. This 3-year multicenter study was conducted on elderly Thai patients with AML, and aimed to evaluate the epidemiology and factors impacting the survival outcome of the patients. From the 235 elderly patients with AML, patients with poor performance status and patients receiving low-intensive therapy had significantly poorer survival outcome. Background: Elderly patients with acute myeloid leukemia (AML) have a poorer prognosis than younger ones. Several factors contribute to the poor outcomes for this patient group. Patients and Methods: This study investigated the epidemiology, clinical characteristics, treatment, and clinical outcomes of elderly Thai patients with AML. This 3-year, prospective, multicenter study was focused on Thai patients with AML aged over 60 years who were diagnosed between 2014 and 2016. Results: Of 680 patients with AML, 235 elderly patients with AML (34.6%) were identified, with a mean age of 70 ± 8 years. Using a 3-group cytogenetic risk classification (favorable, intermediate, and adverse risk), the proportions of patients in each category were 3.6%, 73.8%, and 22.6%, respectively. The median follow-up time for surviving patients was 846 days. The median overall survival (OS) of the patients was 128.2 days (range, 0-1205 days), with a 1-year OS of 13%. From a multivariate analysis, the significant factors associated with an improved long-term OS were patients with an Eastern Cooperative Oncology Group performance status 0 to 2 and those receiving intensive therapy. Conclusion: Our study confirms the high prevalence of AML in elderly patients with generally poor outcomes. Selected patients with a good performance status and those who received intensive induction treatment could have a long-term survival.